The Perceptions and Acceptance of Covid 19 Vaccination among Health Care Workers in Northern India - Ravishekar N. Hiremath; Kasi Viswanath; S. R. Manjunath; Sandhya Ghodke (Current Overview on Disease and Health Research Vol. 7, 2023)
Since the start of the year 2020, the Covid 19 infection has become the biggest nightmare for the entire human race, particularly for medical professionals and other members of the general population. The decision to prioritise vaccines for HCWs and FLWs will boost warrior morale and spirit in the future. This study was a preliminary attempt to identify and address any vaccine hesitancy factors among HCWs. Although almost all had volunteered for vaccination, the majority of HCWs had limited knowledge of the vaccine due to the recent vaccine rollout and the lack of detailed research findings. All measures must be taken, including intensive IEC activities aimed at HCWs and the general public on a regular basis, to improve vaccine knowledge. In an era of misinformation, a strong communication policy is highly recommended, as social media plays an important role in spreading both true and false messages, jeopardising the entire gains of successful vaccination and herd immunity. HCWs to serve as role models for the general public and patients, increasing vaccine acceptance among them.